OPTIMASI PEMANFAATAN LUMPUR AKTIF UNTUK MENURUNKAN KADAR COD MENGGUNAKAN METODE DESAIN EKSPERIMEN TAGUCHI (INVANTRI (Inovasi Dan Pengelolaan Industri), 2022)
Abstract PT. XYZ is a private sugar factory in Lamongan Regency, East Java. The resulting product is sugar, besides that the sugar production process cannot be separated from liquid waste. PT. XYZ often has problems in the treatment of WWTP (Wastewater Treatment Plant) at the input in the BE pond (Equalization Tank). Influent in the BE pond (Equalization Tank) often occurs levels of COD (Chemical Oxygen Demand) that do not match the company's quality standards because the influent input is sometimes too large. The purpose of this study was to improve the quality of the influent product to match the company's quality standards with aspects of activated sludge utilization in BE ponds (Equalization Tank). The taguchi method is used as a method to improve and improve quality and analyze the factors that influence the quality of the influent, including the volume of activated sludge, the length of the aerator running, the volume of waste, the interval between activated sludge added and observed. Taguchi standard orthogonal matrix L8(27) used the objective function 'the value is getting smaller (closer to the desired 0)'. The results of the analysis of variance (ANOVA) obtained that the dominant factor affecting the quality of the influent was the volume of waste (C), while based on the Taguchi method, the most optimal experimental results resulted in a combination of 100 ml activated sludge volume, 5 hours aerator running time, 1 liter waste volume, the gap between activated sludge was added and observed for 5 hours.